Corrosion of Carbon Steel in Hybrid N-Methyl-2-Pyrrolidone - Monoethanolamine Solutions for Carbon Dioxide Absorption Unit Application - Tan, P.Y. (Institute of Physics Publishing, 2020)
Corrosion is defined as degradation or deterioration of material and its properties interact with environment by electrochemical and chemical reaction. It not only causes monetary loss but also potential issues for human health. This study investigates the corrosion rate of carbon steel when immersed in hybrid n-methyl-2-pyrrolidone (NMP) - monoethanolamine (MEA) solutions in comparison with immersion in the conventional aqueous MEA solution. ASTM G31 was adopted in research design methodology and the corrosion rate was evaluated via mass loss measurement. The corrosion rate of carbon steel at 35 days was lowered by approximately 14 when NMP partially replaced the water in the MEA solution. Meanwhile, the corrosion rate was lowered by approximately 20 when NMP fully replaced the water in the MEA solution. Therefore, the corrosion of carbon steel in MEA solution was found to be reduced when NMP partially or fully replaced the composition of water. Â© Published under licence by IOP Publishing Ltd.